Kidung Bhramara Sangupati Analisis Semiotik - I Wayan Juliana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Kidung Bhramara Sangupati is one of the many kidung literatures which is widespread in Bali. Kidung Bhramara Sangupati was composed by Ida Pedanda Wanasara from Tabanan. Kidung Bhramara Sangupati tells “I Lyrics” that ask his lover when he dies, so that his lover will sing the song that he wrote as a provision for his death. The Bhramara Sangupati kidung literature is filled with symbolic signs that demand the reader to give an interpretation. The theory used in this research is Michael Riffaterre's semiotic theory which emphasizes heuristic and hermeneutic reading in order to get the meaning of the Kidung Bhramara Sangupati. Heuristic reading is a reading based on linguistic competence (meaning level) and hermeneutic reading, namely reading based on literary competence (signifiance level). From the results of the readings, the results are obtained in the form of a matrix from the Bhramara Sangupati is yoga sastra (yoga through the media of literary creation) built by several models, namely Bhramara (creation) and Sangupati (provision of death).